Aplikasi Pemesanan E-Ticket di Kolam Renang Primer Koperasi Angkatan Laut (Primkopal) Lanmar Jakarta Berbasis Android dengan Metode First Come First Serve Menggunakan Android Studio dan Firebase - Nurwansyah, Andi; Faizah, NM; Ginting, Winton (Computer Journal, 2023)
Primkopal Lanmar Jakarta Swimming Pool is one of the swimming pools under the auspices of the Jakarta Marine Base Marine Cooperative Primary which is engaged in business, in the form of Pool Rentals. Until now, Pool Ticket Ordering is still done manually. The method used by the Primkopal Swimming Pool management is currently inefficient. Therefore, this study has the objectives, (1) Designing a swimming pool ticket booking application that can be easily and quickly accessed by customers via gadgets, (2) Designing a swimming pool ticket ordering application that can be used by employees to update availability status information swimming pool, and (3) Designing a swimming pool ticket booking application that can provide an overview of the facilities offered by Primkopal Swimming Pool. From this goal, the authors built and designed an Android-based application for ordering e-tickets at the Lanmar Jakarta Navy Cooperative Primary Pool (Primkopal) with the First Come First Serve method using Android Studio and Firebase. The final result of this research is to improve the quality and service for prospective purchasers of Primkopal Lanmar Jakarta Swimming Pool Tickets.